ارتفاع مناسيب المياه الجوفية تحت تأثير الري السطحي في مشروع ري سد نهر الكبير الشمالي - الأسعد علي محمد; إبراهيم عدنان محمد; علاء الدين محمد دريد (Latakia University Journal -Engineering Sciences Series, 2019)
تبلغ مساحة المنطقة المدروسة حوالي 5000 هكتار، وهي تشغل الجزء الشمالي من سهل جبلة، ولها أهمية اقتصادية كبيرة. تنمو فيها بساتين الحمضيات والزيتون، وتزرع الخضراوات بأنواعها. تتألف توضعات الرباعي من رمال, وحجر رملي، سماكتها 10 – 20 م، وناقليتها المائية 200 – 400 م2 / يوم، كما تتألف من كونغلوميرا, تنتشر في أودية الأنهار، وتصل سماكتها إلى أكثر من 50 م وناقليتها المائية 50 – 100 م2 / يوم. يشكل مارل البليوسين طبقة كتيمة ذات انتشارإقليمي، سماكتها كبيرة 300 – 350 م، تتوضع تحت صخور الرباعي, والبليوسين الحاملة للمياه الحرة. تتغير سماكة منطقة التهوية بحسب الظروف الطبغرافية, والهيدروجيولوجية. فتبلغ أكبر قيمة لها 10 – 15 م في المناطق المرتفعة، وتتناقص إلى أقل من متر في الأودية, والسهول الشاطئية، وعموماً يرتفع منسوب المياه الجوفية في الشتاء والربيع, ويشكل المستنقعات الموسمية. تتغذى المياه الجوفية على حساب تسرب مياه الأمطار, ومياه الري. وارتفع منسوب المياه الجوفية نتيجة لزيادة التغذية من تسرب مياه الري، وبسبب قلة كفاءة شبكة الصرف الطبيعي والاصطناعي. وتشكلت المستنقعات الدائمة والموسمية فشملت مساحة إجمالية، بلغت 225 هكتاراً من الأراضي الزراعية الخصبة. المياه الجوفيـة صـالحة للري، ويمكن تخفيض منسـوبها عن طريق اسـتثمارها بوسـاطة آبار قليلة العمق ( 5 – 15 متراً )، والالتزام بمعدلات الذي المدروسة، مع ضرورة صيانة شبكات الري والصرف، بهدف تجفيف المستنقعات وتوفير كمية كبيرة من مياه الري، لاستخدامها في مجالات أخرى. The under study area forms an important part of Jableh plains and it has great economic importance. Citrus and olive orchids are available in the plains and various kinds of vegetation are planted. The total area of the plains is about 5000 ha. The quaternary deposits consist of sand and sand stone. Its thickness varies from 10 – 20 meters; its transmissivity reaches 200 – 400 m2/ day. It also has conglomerate in the river vallies which thickness goes up to 50 meters; its transmissivity reaches to 50 – 100 m2 / day. However, the Pliocene deposits are just marl, which is of high regional spread. It is 300 – 350 meters thick, and forms an aquitard under the quaternary aquifer. Both the quaternary and Pliocene deposits, which hold the water, form an unconfined aquifer. The thickness of the aeration zone varies from one place to the other according to both the topographical and hydrogiological conditions. Thus it reaches its highest level which is 10 – 15 meters in high areas, and starts decreasing to reach less than a meter in the vallies, and the coastal plains. However the level of the groundwater increases in winter and spring, and spread bogs. The main source of the groundwater is the infiltration of the rain and irrigation water. The water-table level has increased due to the excessive supply of the percolated irrigation water and to the ineffectiveness of the drainage system. Permanent and seasonal swamps have come to existence covering 225 ha. of fertile agricultural land. The groundwater can be used for irrigation purposes and the water-table level can be reduced by pumping the underground water through few wells ( 5 to 15 meters deep). Also, the adherence to recommended rates of irrigation, the good maintenance of the irrigation and drainage system will lead to the drying of the bogs and to make large amount of irrigation water available for further utilization.